(untitled) (Research, Society and Development, 2021)
We aimed to investigate the autonomic responses to cold pressor test (CPT) in individual with different levels of muscle strength. 57 male subjects participated in the study. Volunteers were divided in tertiles according to their level of relative handgrip strength as Low (LS), Medium (MS) and High (HS). For the CPT the volunteers remained seated in resting for 15 minutes and inserted the right hand in cold water for two minutes. Blood pressure (BP) measurements were taken at rest, during CPT and during recovery. HRV was continuously recorded during the entire protocol. All three groups had similar BP variation, with the values of systolic blood pressure (SBP) increasing during CPT and diminishing during recovery until the third minute. At the first CPT minute LS group showed a substantial increase in low-frequency (LF) activity and a diminished high frequency (HF). LS also presented higher and lower values of LF and HF, respectively, than MS group at the first CPT minute. HS showed an increased vagal activity during recovery. In conclusion, individuals from LS presented similar BP responses to CPT than MS and HS groups but with higher sympathetic activation. HS individuals presented an elevated vagal activity during recovery.